Third-line treatment options in metastatic pancreatic cancer patients: a real-world study - Lu, Hong-Rui; Zhu, Peng-Fei; Deng, Ya-Ya; Chen, Zhe-Ling; Yang, Liu (Frontiers in Oncology, 2023)
Background There are currently no standard therapy regimens for the third-line treatment of metastatic pancreatic cancer (mPC) patients. The aim of the present study was to compare the efficacy and safety of different third-line therapy regimens for mPC in the real-world. Methods This study retrospectively analyzed mPC patients admitted to Zhejiang Provincial People’s Hospital between June 2013 and January 2023. All patients’ diagnoses were pathologically confirmed and their treatment was continued after the second-line therapy failed. The primary study endpoints included median overall survival (mOS), median progression-free survival (mPFS), and disease control rate (DCR). Results A total of 72 patients were enrolled in the study. Of these, 36 patients received chemotherapy alone, 16 received chemotherapy combined with targeted therapy or immunotherapy, 14 received chemotherapy-free antitumor therapy, and six received palliative care. The mPFS value for these groups was 4.40 months, 5.20 months, 2.33 months, and 0.80 months, respectively. The mOS value was 6.90 months, 5.90 months, 3.33 months, and 0.80 months, respectively. The DCR was 33.4%, 31.3%, 21.4%, and 0.0%, respectively. Overall, there were significant differences in prognosis between the palliative care group and the other treatment groups (mOS, P < 0.001; mPFS P < 0.001; DCR, P < 0.001). The differences among the mPFS, mOS, and DCR for different antitumor therapy regimens were not statistically significant. Compared to the chemotherapy alone group, the chemotherapy combined with targeted therapy or immunotherapy group experienced more adverse events (100% vs. 75.0%; P = 0.002). Chemotherapy combined with targeted therapy or immunotherapy was associated with a higher risk of grade 3/4 hyperaminotransferemia compared to chemotherapy alone (31.3% vs. 0.0%; P = 0.020) and chemotherapy-free antitumor therapy (31.3% vs. 0.0%; P = 0.020). Conclusions Third-line antitumor therapy can prolong the survival time of patients with mPC. Targeted therapy or immunotherapy failed to further improve survival benefits based on chemotherapy results. Patients who underwent the third-line treatment with good physical status and family history of cancer were independent prognostic factors for longer mOS. The sequencing of fluorouracil and gemcitabine in the front-line therapy did not affect third-line mOS.